2011
DOI: 10.5488/cmp.14.33604
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the structure of tethered chain molecules as predicted by density functional approach

Abstract: We use a version of the density functional theory to study the changes in the height of the tethered layer of chains built of jointed spherical segments with the change of the length and surface density of chains. For the model in which the interactions between segments and solvent molecules are the same as between solvent molecules we have discovered two effects that have not been observed in previous studies. Under certain conditions and for low surface concentrations of the chains, the height of the pinned … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…In the previous paper [50] we have studied the changes in the structure of tethered chains in contact with a one-component fluid. We have shown that in the region of mediate grafting coverages, a minimum on the curve ln(h) vs ln(ρ * c ) can develop.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous paper [50] we have studied the changes in the structure of tethered chains in contact with a one-component fluid. We have shown that in the region of mediate grafting coverages, a minimum on the curve ln(h) vs ln(ρ * c ) can develop.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous paper [50] the effect of strong adsorption of one-component fluid on the height of the bonded layer has been investigated. In this work we employ the density functional theory to describe the short grafted chains immersed by a mixture of two liquids.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the grafted chains did not practically affect one another, and they assumed unperturbed configurations. For medium-covered substrates, the height fell to a minimum [62]. With a further increase of the grafting density, the brush height increases as in the predicted scaling theories [19].…”
Section: Thickness Of Polymer Layermentioning
confidence: 54%
“…Such a relation accurately approximates the data obtained for dense brushes. However, density functional studies [62] showed that the behavior of sparse brushes can be completely different. For very low surface densities of tethered chains, the brush height remained almost constant.…”
Section: Thickness Of Polymer Layermentioning
confidence: 99%
See 1 more Smart Citation